2017
DOI: 10.1111/bjd.15406
|View full text |Cite
|
Sign up to set email alerts
|

Diminished protein-bound ω-hydroxylated ceramides in the skin of patients with ichthyosis with 12R-lipoxygenase (LOX) or eLOX-3 deficiency

Abstract: DEAR EDITOR, Autosomal recessive congenital ichthyoses (ARCIs) are a group of hereditary skin disorders. The disease phenotype is associated with an impaired epidermal barrier leading to increased transepidermal water loss, temperature instability and hypernatraemic dehydration in infancy. 1 ARCIs are known to be caused by mutations in at least nine different genes, which encode proteins involved in the formation of the epidermal barrier. 2 Two of these genes, ALOX12B and ALOXE3, code for the epidermal lipoxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…These observations help to clarify the function of 12R-LOX in the context of CLE formation and maturation. Similar to previous reports, 14,27 12R-LOX was found in the current study to be required for most CLE-CE cross-linking. However, this is the first report that CLE formation occurs independently of 12R-LOXedependent CLE-CE cross-linking.…”
Section: Discussionsupporting
confidence: 93%
“…These observations help to clarify the function of 12R-LOX in the context of CLE formation and maturation. Similar to previous reports, 14,27 12R-LOX was found in the current study to be required for most CLE-CE cross-linking. However, this is the first report that CLE formation occurs independently of 12R-LOXedependent CLE-CE cross-linking.…”
Section: Discussionsupporting
confidence: 93%
“…As shown in Fig 1a, CLE plays an indispensable role in combining the corneocyte envelope with extracellular lamellar lipids. It has been reported that the amount of stratum corneum ceramides in patients with ichthyosis or atopic dermatitis is lower than in normal subjects [19, 21, 28]. This paucity of ceramides in these diseases is involved in the decrease of ceramide OS comprising the CLE [4].…”
Section: Discussionmentioning
confidence: 99%
“…We have clarified that SDR9C7 catalyzes the critical dehydrogenation of oxidized CerEOS to synthesize a highly reactive epoxy-enone derivative that is esterified in CerEOS [14]. The epoxy-enone is known to link nonenzymatically to proteins [14,80,81]. A plain a/bunsaturated ketone (enone) reacts with amino acid residues, cysteine, histidine, and lysine via Michael addition [82][83][84].…”
Section: Dehydrogenation and Binding Of Acylceramides To Ccementioning
confidence: 99%